Effects of xenon-ion irradiation on the tribological properties and crystal structure of titanium and its alloy Ti6Al4V. (April 2021) - Budzyński, P.; Kamiński, M.; Surowiec, Z.; Wiertel, M.; Skuratov, V.A.; Korneeva, E.A.
Abstract: Tribological properties of titanium and alloy Ti6Al4V are changed by the irradiation with 160 MeV swift xenon ions. At the beginning of the tribological test, the friction coefficient of titanium is reduced. As the test of titanium proceeds, an unconventional two-step increase in its value is observed. The irradiation causes oscillating changes in the crystal lattice parameters of titanium and Ti6Al4V. These unconventional changes result from the annealing and evolution of radiation defects during irradiation with a high fluence of Xe ions. The two-step changes in the friction coefficient of titanium and the unconventional changes in the crystal lattice parameters of Ti and Ti6Al4V following the swift Xe-ion irradiation have been observed for the first time. Highlights: Two-step changes in the friction coefficient of Ti irradiated with swift Xe ions. Lattice parameters of Ti6Al4V undergo oscillating changes with increasing ion dose. This effect is the result of annealing and evolution of radiation defects.